(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2010)
An electroanalytical method has been developed for the determination of zinc in whole blood by differential pulse anodic stripping voltammetry (DPASV) on a hanging mercury drop electrode (HMDE). The best conditions were found to be electrolyte support perchloric acid 0.02M, an accumulation potential of -1150 mV, and an accumulation time of 60 s. The optimum value of stirring rate was determined to be 400 rpm. The correlation coefficient and relative standard deviation were 0.9999 and 3.96% respectively with a detection limit of 0.86 Âµg L-1. Zinc levels in whole blood samples of 53 healthy subjects living in Tlemcen (west Algeria).